2010
DOI: 10.1016/j.ssc.2009.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Electronic properties of novel 6 K superconductor LiFeP in comparison with LiFeAs from first principles calculations

Abstract: Very recently the new low-temperature (T C ~ 3K) superconductor (SC) SrPd 2 Ge 2 has been reported. This compound is isostructural with curently intensively studied group of so-called "122" SC's (based on tetragonal AM 2 Pn 2 phases, where A are Sr, Ba; M are d metals and Pn are pnictogens: As or P), but it is pnictogen-free. Here, by means

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 53 publications
2
13
0
Order By: Relevance
“…The obtained Fermi surfaces ( Fig. 4) are similar to previous calculations [35]. Although angleresolved photoemission results have suggested quite different Fermi surfaces with no interband nesting in LiFeAs [33], more recent bulk measurements of dHvA oscillations reveal quasi-nested hole and electron sheets [37] in a good agreement with the calculations.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…The obtained Fermi surfaces ( Fig. 4) are similar to previous calculations [35]. Although angleresolved photoemission results have suggested quite different Fermi surfaces with no interband nesting in LiFeAs [33], more recent bulk measurements of dHvA oscillations reveal quasi-nested hole and electron sheets [37] in a good agreement with the calculations.…”
supporting
confidence: 88%
“…In LiFeAs, antiferromagnetic fluctuations have been observed [26,27] and fully gapped superconductivity has been demonstrated by several experiments [28][29][30][31][32][33], but no information has been reported for the pairing state in LiFeP. Bandstructure calculations show that the two materials exhibit similar Fermi surface shapes [34,35]; quasi-cylindrical hole sheets near the zone center and two warped electron sheets near the zone corner.Here we report on precision measurements of the magnetic penetration depth λ(T ) in single crystals, which demonstrate a nodal gap state in LiFeP in sharp contrast to the nodeless state in LiFeAs. Our analysis based on accumulated λ(T ) data in the 1111, 122, and 111 series of superconductors, indicates that the nodal state is induced when h P n is below a threshold value.…”
mentioning
confidence: 99%
“…It was found that the order parameter Δ 1 = 1.5 meV in this compound is associated with hole car riers, while order parameter Δ 2 = 2.5 meV is associated with electron like charge carriers [15,16]. The two band nature of the order parameter in LiFeAs is also confirmed by heat capacity measurements [17] and by ab initio calculations [18]. The existence of two order parameters with different degrees of anisotropy leads to different physical properties [19].…”
mentioning
confidence: 63%
“…The highest temperature of doped SmFeAsO 1−x F x systems is 55 K for x = 0.2 [4,5]. The Fermi surface * E-mail: imasker@eng.ankara.edu.tr of SmFeAsO 1−x F x is formed by three concentric hole cylinders at the Γ point of Brilloun zone and a small hole cylinder near the zone boundary [6,7]. Many-band character of superconducting state of SmFeAsO 1−x F x was confirmed by ARPES [8] and de Haas-van Alphen experiments [9].…”
Section: Introductionmentioning
confidence: 99%
“…The main peculiarity of superconductivity in Fe-based compounds is related to the multiband character of state [4,6,7]. It is useful to note that the multiband Bardeen-Cooper-Schrieffer theory for Fe-based superconductors was suggested in recent studies [10,11].…”
Section: Introductionmentioning
confidence: 99%